A New Approach Toward Extreme Thermal Stability of Femtosecond Laser Induced Modifications in Glasses - Ktafi, Imane; Kong, Jing; Cavillon, Maxime; Poumellec, Bertrand; Yembele, Maureen; Valois, Renaud; Allix, Mathieu; Peng, Gang‐Ding; Lancry, Matthieu (Laser & photonics reviews, 2025)
Imprinting thermally stable transformations by femtosecond laser in glass would benefit the development of optical sensors dedicated to harsh environments including combustors, nuclear reactors, aircraft engines, or metal/ceramic manufacturing processes. While glass brings undeniable assets over refractory crystalline materials like shaping ability (e.g., optical fiber form), one key challenge is to prevent the erasure of induced transformations at high temperatures and for long periods. In this article, the role of glass composition and viscosity to achieve modifications stable at high temperatures is first reviewed, providing a comprehensive roadmap for engineers in optics and photonics. While silica appears to be the candidate of choice, it is revealed that binary aluminosilicates can compete and sometimes surpass it. The hypothesis is formulated and investigated that a hybrid glass‐crystalline nano‐structuring can imprint ultra‐stable modifications inside glass. Laser‐induced modifications in Al2O3‐SiO2 and ZrO2‐Al2O3‐SiO2 glasses reveal a partial crystallization, shaped into a lamellar structure and orientable with laser light polarization. These birefringent structures can withstand temperatures up to 1300 °C for 30 minutes. Even after erasure, a positive index contrast persists, up to 1650 °C for binary 60Al2O3‐40SiO2 (mol%). This is the first observation of this kind of persisting index contrast, paving the way to ultra‐stable glass‐based optical waveguiding. Femtosecond laser irradiation inside Al2O3‐SiO2 and ZrO2‐Al2O3‐SiO2 glasses can induce polarization‐controlled birefringent nanostructures, along with local precipitation of refractory nanocrystals like tetragonal ZrO2 or mullite. These structures yield a persisting positive index contrast with extraordinary thermal stability (>1600 °C), opening a route to the design of optical functions embedded in glass and operating under extreme environments.